Delimited control and computational effects. Issue 1 (January 2014) - DOWNEN, PAUL; ARIOLA, ZENA M.
Abstract We give a framework for delimited control with multiple prompts, in the style of Parigot's λμ-calculus, through a series of incremental extensions by starting with the pure λ-calculus. Each language inherits the semantics and reduction theory of its parent, giving a systematic way to describe each level of control. For each language of interest, we fully characterize its semantics in terms of a reduction semantics, operational semantics, continuation-passing style transform, and abstract machine. Furthermore, the control operations are expressed in terms of fine-grained primitives that can be used to build well-known, higher-level control operators. In order to illustrate the expressive power provided by various languages, we show how other computational effects can be encoded in terms of these control operators.